Switched Photocurrent on Tin Sulfide‐Based Nanoplate Photoelectrodes. Issue 4 (27th January 2017) - Chen, Hongjun; Lyu, Miaoqiang; Zhang, Meng; Feron, Krishna; Searles, Debra J.; Dargusch, Matthew; Yao, Xiangdong; Wang, Lianzhou
Abstract: A new type of SnS2 nanoplate photoelectrode is prepared by using a mild wet‐chemical method. Depending on the calcination temperatures, SnS2 ‐based photoelectrodes can either retain their n‐type nature with greatly enhanced anodic photocurrent density (ca. 1.2 mA cm −2 at 0.8 V vs. Ag/AgCl) or be completely converted into p‐type SnS to generate approximately 0.26 mA cm −2 cathodic photocurrent density at −0.8 V vs. Ag/AgCl. The dominance of sulfur and tin vacancies are found to account for the dramatically different photoelectrochemical behaviors of n‐type SnS2 and p‐type SnS photoelectrodes. In addition, the band structures of n‐type SnS2 and p‐type SnS photoelectrodes are also deduced, which may provide an effective strategy for developing SnS2 /SnS films with controllable energy‐band levels through a simple calcination treatment. Abstract : Small plates : A simple chemical method is developed to prepare SnS2 nanoplate photoelectrodes. Depending on the calcination temperatures, the SnS2 photoelectrodes can either remain as n‐type SnS2 with greatly enhanced anodic photocurrent or be completely converted into p‐type SnS to generate cathodic photocurrent.